The effects of HAPA theory-based case management in patients with metabolic dysfunction-associated steatotic liver disease - Jia Mei; Yuncai Xie; Pingping Huang; Yudi Jin; Xia Wang; Ying Chen (Annals of Hepatology)
Introduction and Objectives: Metabolic dysfunction-associated steatotic liver disease (MASLD) is the most common liver disease affecting people's health, with its incidence increasing year by year. This study aims to determine the effects of Health Action Process Approach (HAPA)-based health management on patients diagnosed with MASLD. Patients and Methods: 204 MASLD patients were selected from the hospital's physical examination center from January 1, 2023, through April 1, 2023. Patients are randomly assigned to two groups (n = 102 each) using an envelope-based. Individuals in the experimental group received case management based on the HAPA theory, while standard health management was employed for control group patients. All subjects were monitored over a 6-month period, comparing body mass index (BMI), waist-to-hip ratio (WHR), levels of liver function (AST, ALT), blood lipid levels (total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and health behaviours (as assessed with the HPLP-II health promotion lifestyle scale) before and after the intervention. Results: Post-intervention, the experimental group showed significant improvement in fatty liver (P < 0.01) and reductions in biochemical indices, BMI, and WHR levels (P < 0.05), and a corresponding improvement in HDL-C levels (P < 0.001), compared to the control group. Additionally, patients in the experimental group exhibited significantly better health behaviour scores related to stress management, exercise, diet, and health responsibility compared to controls (P < 0.01). Conclusions: HAPA theory-based case management can improve blood lipid profiles, liver function, and health-related behaviours in MASLD patients, highlighting its potential as an effective management strategy for this condition.